Touristic Resources and Tourism Development Prospects in Gegharkunik Region of the Republic of Armenia - Tovmasyan, Gayane; Gevorgyan, Marine («Տնտեսագետ» հրատ․)
Gegharkunik region is situated in the eastern part of the country and was established in 1995. The region has beautiful cultural and natural resources, based on which many tourism routes may be created. The main methods used in the article are: micro and macro analyses, statistical methods, correlation analysis, SWOT analysis. The article analyzes the main tourism assets of the region. Besides, the main socioeconomic indicators, tourism infrastructure, and the current state of tourism in the region were analyzed. SWOT analysis was applied for revealing key obstacles hindering tourism development. Based on it, some steps were offered, such as the creation of new tourist routes, the elaboration of a sustainable tourism development plan, improvement of marketing activities, creation of a typical tourist brand for the region, improving statistical recording, organization of new festivals, etc. The results may be useful for governmental and local authorities, as well as the private sector, for improving their tourism development policies.
Keywords: Regional developments